A novel discrete multi-objective particle swarm optimisation (MOPSO) technique for optimal hybrid power filter compensator schemes. (21st August 2009) - Sharaf, Adel M.; El-Gammal, Adel A.A.
This paper presents a novel algorithm for a discrete search optimisation and an approach to solve the problem of the hybrid power filter compensator with the design of C-type filter and fixed capacitor bank using discrete multi-objective particle swarm optimisation (MOPSO) method. This novel optimisation approach, a multi-objective particle swarm optimisation (MOPSO) method is implemented to tackle a number of conflicting search goals that define the complex optimal filter design problem. The paper presents the selection with conflicting objective functions and a compromising selection criterion: 1) minimum change in the fundamental frequency load bus voltage under steady state conditions, 2) minimum feeder current for maximum AC system grid capacity release, 3) minimum fundamental frequency utilisation feeder active and reactive power losses, due to reduced fundamental RMS current magnitude, 4) minimum dominant harmonic current penetration into the host electric grid system, 5) maximum harmonic current absorption by the hybrid harmonic power filter with the fixed capacitor bank, 6) minimum harmonic voltage distortion at the point of common coupling or load bus.